A systematic mapping study on risk management in the export development of high-tech products. Issue 3 (2nd October 2019) - Tanabandeh, Maryam; Salajegheh, Sanjar; Pourkiani, Masoud
Abstract : Purpose: This paper aims to characterize and identify the existing research on risk management in the export development of high-tech products. Design/methodology/approach: The authors conducted a systematic mapping study to identify and analyze related literature. The authors identified 96 primary studies, dated from 2000 to 2018 and classified them with respect to research focus, types of research and contribution. Findings: A total of 32 studies were identified and mapped, synthesizing the available evidence on risk management in the export development of high-tech products. "Currency risk" with 13 articles is the dominant research focus. Regarding the research type, "Solution proposal" is the most frequently used research type. "Case study", "Regression analysis" and "Survey", respectively, were the most used research methods. However, "FANNIS", "FAHP" and "Discussion paper" were used less often. "Solution proposal" was the most common research type between 2000 and 2018. Further, the number of publications has declined between 2010 and 2012. Originality/value: This mapping study provides the first systematic exploration of the state-of-art on risk management research in the export development of high-tech products. The existing body of knowledge is limited to a few high-quality studies.